Comparative Efficacy of Iron Chelation Therapies on Cardiac and Liver Iron Levels in Thalassemia Patients: A Systematic Review and Network Meta-Analysis - Abdulsalam Aleid; Dhiyaa Almu; Nada Almuwalad; Muhannad Alruwaili; Khalid Alaryani; Zeyad Alhaboob; Mohammed Alwabari; Saja Albenayyan; Wahaj AlHarbi; Abbas Shamsan; Abbas Al Mutair (Dr. Sulaiman Al Habib Medical Journal)
Beta-thalassemia major is a genetic disorder that causes hemolytic anemia and requires regular blood transfusions, leading to iron overload in organs such as the liver and heart. This iron accumulation can result in severe health issues, including cardiac complications and liver diseases. Although iron chelation therapy is vital for managing iron overload, the effectiveness of various chelation therapies remains to be investigated. A thorough literature search was conducted in January 2024 across databases, including PubMed, Web of Science, Cochrane Library, and Scopus. Data was analyzed using R software, employing packages for network meta-analysis (NMA). Continuous data was assessed using mean difference (MD) with 95% confidence interval (CI), with random-effect and fixed-effect models applied as appropriate. This network meta-analysis involved 17 studies. In cardiac MRI T2*, deferasirox (DFX) outperformed other therapies (MD = 1.75, 95%CI [0.34, 3.15]). The combination of DFX and deferiprone (DFP) had the greatest effect on ferritin levels DFP (MD = −1244.68, 95%CI [−2312.69, −176.68]). The NMA showed significant increase in liver MRI T2* achieved by DFO + DFP in comparison to DFO (MD = 2.19, 95%CI [0.42, 3.96]). By contrast, no significant differences were observed across treatments for liver iron concentration. This meta-analysis demonstrates that the effectiveness of iron chelation therapy for beta-thalassemia major varies, with DFX outperforming in cardiac MRI T2* improvement and a combination of DFO and DFP exhibiting a better result in liver MRI T2* increase. Future research should explore larger samples and diverse patient-reported outcomes to enhance understanding of the impact of these therapies on patient health and quality of life.